The Role of Macrophages in HIV-1 Persistence and Pathogenesis - Kruize, Zita; Kootstra, Neeltje A. (Frontiers in Microbiology, 2019)
Current antiretroviral therapy (ART) effectively suppresses Human Immunodeficiency Virus type 1 (HIV-1) in infected individuals. However even long term ART does not eradicate HIV-1 infected cells and the virus persists in cellular reservoirs. Beside memory CD4+ T cells, cells of the myeloid lineage, especially macrophages, are believed to be an important sanctuary for HIV-1. Monocytes and macrophages are key players in the innate immune response to pathogens and are recruited to sites of infection and inflammation. Due to their long life span and ability to reside in virtually every tissue, macrophages have been proposed to play a critical role in the establishment and persistence of the HIV-1 reservoir. Current HIV-1 cure strategies mainly focus on the concept of “shock and kill” to purge the viral reservoir. This approach aims to reactivate viral protein production in latently infected cells, which subsequently are eliminated as a consequence of viral replication, or recognized and killed by the immune system. Macrophage susceptibility to HIV-1 infection is dependent on the local microenvironment, suggesting that molecular pathways directing differentiation and polarization are involved. Current latency reversing agents (LRA) are mainly designed to reactivate the HIV-1 provirus in CD4+ T cells, while their ability to abolish viral latency in macrophages is largely unknown. Moreover, the resistance of macrophages to HIV-1 mediated kill and the presence of infected macrophages in immune privileged regions including the central nervous system (CNS), may pose a barrier to elimination of infected cells by current “shock and kill” strategies. This review focusses on the role of monocytes/macrophages in HIV-1 persistence. We will discuss mechanisms of viral latency and persistence inmonocytes/macrophages. Furthermore, the role of these cells in HIV-1 tissue distribution and pathogenesis will be discussed.